Research on the optimization method of integrated energy system operation with multi-subject game - Wang, Yongli; Liu, Zhen; Cai, Chengcong; Xue, Lu; Ma, Yang; Shen, Hekun; Chen, Xin; Liu, Lin (Energy (Oxford), 2022)
The construction of integrated energy system can effectively improve energy efficiency and reduce carbon emission, which is of great significance to energy sustainable development. This paper proposes an integrated energy system operation optimization method based on cooperative game, which can effectively reduce the energy cost and carbon emissions of the system, and encourage different subjects to participate in the overall coordinated and optimized operation of the system. Firstly, combined with cooperative game theory, a cooperative game model of integrated energy system with cost and carbon emission as objectives is established. Secondly, a profit distribution method combining improved Shapley value and nucleolus method is proposed. Finally, an improved Non-dominated Sorting Genetic Algorithm is proposed to solve the cooperative game model, which greatly improves the solving efficiency. The example shows that the cooperative mode saves 26.86% of the cost and reduces 39.42% of the carbon emission compared with the independent operation. At the same time, the scientific and effective benefit distribution method proposed in this paper is verified from the overall, individual and alliance perspectives. •Analyzed the energy architecture of different operation modes of integrated energy system.•Constructed a cooperative game model of integrated energy system.•Proposed a benefit distribution model based on the improved Shapley value and nucleolus method.•Study the influence of system cost and carbon emission by energy price fluctuation under different models.